An Analysis of the Islamic Religious Education Curriculum in Religious Schools and Colleges within the Framework of the National Education System Law of 2003 - Rupiah; Amin, Alfauzan; Rohimin; Suradi, A (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2024)
Curriculum in general is a set of plans and arrangements regarding objectives, content and learning materials as well as methods used as guidelines for implementing learning activities to achieve certain educational goals. Islamic religious education is one of the government's efforts to educate the nation's children based on Islamic religious values and noble morals. The aim of this research is to look in more detail at the position of the PAI curriculum in the National Education System Law no. 20 of 2003; three basic principles are used as the basis for PAI: the juridical basis, which consists of an ideal basis, namely the basic philosophy of the State of Pancasila, the first principle, belief in the one, and only God. Structural/constitutional basis, namely constitution (UUD) 1945 Chapter Religious basis, which comes from Al-Qur’an and Hadith. For Muslims, Islamic religious education is mandatory. The psychological basis is the basis related to the psychological aspects of people's lives. The position of Islamic Religious Education in the National Education system is explained in Article 15 of the National Education System Law no. 20 of 2003; in Article 12, section (1) religious education is taught by religious teachers who are in accordance with the students' religion. To fulfill students' rights to religious education, Article 37 paragraph (1) states that the primary and secondary education curriculum must contain religious education, paragraph 2. The higher education curriculum must include religious education, citizenship education, and language. This means that PAI teachers and lecturers have a strong foundation for developing the Islamic Religious Education teaching process in schools/madrasahs and universities